2004
DOI: 10.1210/jc.2003-031089
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Ischemic Heart Disease and All-Cause Mortality in Subclinical Hypothyroidism

Abstract: We investigated possible associations between subclinical hypothyroidism and atherosclerotic diseases (ischemic heart disease and cerebrovascular disease) and mortality. Of 2856 participants (mean age 58.5 yr) in a thyroid disease screening between 1984 and 1987, 257 subjects with subclinical hypothyroidism (TSH > 5.0 mU/liter) and 2293 control subjects (TSH range 0.6-5.0 mU/liter) were analyzed. In the baseline cross-sectional analysis, subclinical hypothyroidism was associated with ischemic heart disease ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
261
6
13

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(300 citation statements)
references
References 29 publications
18
261
6
13
Order By: Relevance
“…There are some other reports that studied in smaller number of patients with dyslipidemia and reported 6.8% (2.2% and 4.6%, overt hypothyroidism and subclinical hypothyroidism, respectively) in United Kingdom [6], 7.8% (2.5% and 5.3%) in United States [7], and 7.2% (2.8% and 4.4%) in Greece [9]. Thus, the percentage in our study was comparable to previous studies in the subjects with dyslipidemia, but not as high as that in the studies recently reported in Japanese population [25,26]. Several reasons can be described.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There are some other reports that studied in smaller number of patients with dyslipidemia and reported 6.8% (2.2% and 4.6%, overt hypothyroidism and subclinical hypothyroidism, respectively) in United Kingdom [6], 7.8% (2.5% and 5.3%) in United States [7], and 7.2% (2.8% and 4.4%) in Greece [9]. Thus, the percentage in our study was comparable to previous studies in the subjects with dyslipidemia, but not as high as that in the studies recently reported in Japanese population [25,26]. Several reasons can be described.…”
Section: Discussionsupporting
confidence: 85%
“…Several reasons can be described. First of all, we performed multi-center study whose institutions distribute all over Japan, whereas Nagasaki [25] or Suita [26] is a single city. In addition, there are some resources to obtain the clinically important frequency of subclinical hypothyroidism in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, an increased number of prospective population-based cohort studies (100,138,140,158,(161)(162)(163)(164)(165)(166)(167) (A,A,A,A,A,A,A,A,A,B,B), have reported conflicting results on the potential relationship bet ween SH and cardiovascular disease and mortality. These discrepancies may be due to differences in the populations studied in terms of age, sex, race/ethnicity, life style, TSH cutoffs, differences in confounders adjustments, follow-up period, and selection bias (1) (D).…”
Section: Is Subclinical Hypothyroidism Associated To Cardiovascular Rmentioning
confidence: 99%
“…Previous studies have shown unfavorable effects of overt or subclinical hypothyroidism (SCH; normal free thyroxine (FT4) and elevated thyroid stimulating hormone (TSH)) on cardiovascular disease [1][2][3][4][5][6][7][8][9]. Some studies demonstrated the association of lipid abnormality and atherosclerosis with SCH or overt hypothyroidism.…”
mentioning
confidence: 99%